First head-to-head comparison of effective radiation dose from low-dose 64-slice CT with prospective ECG-triggering versus invasive coronary angiography. Issue 20 (5th July 2009) - Herzog, B A; Wyss, C A; Husmann, L; Gaemperli, O; Valenta, I; Treyer, V; Landmesser, U; Kaufmann, P A
Abstract : Background: Reduction of radiation burden of multidetector computed tomography coronary angiography (CTCA) has remained an important task. Objective: To compare effective radiation dose of low-dose 64-slice CTCA using prospective ECG-triggering versus diagnostic invasive coronary angiography (CA). Methods: 42 patients referred for elective invasive CA owing to suspected coronary artery disease (CAD) were prospectively enrolled to undergo a low-dose CTCA without calcium scoring within the same day before CA. Dose-area product of diagnostic invasive CA and dose-length product of CTCA were measured, converted into effective radiation dose and compared using Mann-Whitney U tests. In addition, accuracy of CTCA to detect CAD (coronary artery narrowing ⩾50%) was assessed using invasive CA as standard of reference. On an intention-to-diagnose basis all non-evaluative vessels were included in the analysis and censored as positive. Results: The estimated mean effective radiation dose was 8.5 (4.4) mSv (range 1.4–20.5 mSv) for diagnostic invasive CA, and 2.1 (0.7) mSv (range 1.0–3.3 mSv) for CTCA (p<0.001). 19 patients (42.9%) had no CAD by invasive CA. 40 (95.2%) patients have been correctly classified as having CAD (23/23) or no CAD (17/19). Over 97% (551/567) of segments were evaluable. Vessel-based analysis revealed sensitivity, specificity, positive and negative predictive value of 94.2% (CI 0.8% to 1.0%), 94.8% (CI 09% to 1.0%), 89.0% (CI 0.8% to 1.0%), 97.4% (CI 09% to 1.0%) and an accuracy of 94.6%. Conclusions: Low dose CTCA allows evaluation of CAD with high accuracy, but delivers a significantly less effective radiation dose to patients compared to diagnostic invasive CA.